Line motivation and learning results in university students - Maytorena Noriega, María de los Ángeles (2004)
The aim of this study was to test a multifactor structure for in-line-evaluation of motivation on specific tasks in u ni versity students. Results showed that the initial motivation explained 12% of the variance of total punctuation of the methodology test and test execution explained 17% of the ending motivation. Therefore, in-line-evaluation model allows instructional prescription to students needs in order to facilitate their leaming and academic success.